PENGARUH UNIT KEGIATAN MAHASISWA (UKM) PRAMUKA TERHADAP PEMBENTUKAN KARAKTER JUJUR MAHASISWA UNIVERSITAS RIAU: (Effect of Unit Program Activity University (SME) Pramuka on the Establishment of High Character Students of Riau University) - Arianto, Jumili (Perspektif Pendidikan dan Keguruan, 2017)
The purpose of National education is to develop the ability and to form the character and dignified civilization in order to educate the life of nation, to develop the students’ potential in order to be a religious man and cautious to the God almighty, noble, healthy, competent, creative, independent, and democratic citizen and responsible. The Indonesian government plan the nation culture and character development begun by the declaration of education of culture and character of nation as a national movement in the beginning of january 2010. This plan is reconfirmed in the president’s speech on the National Education Day May 2, 2010. The purpose of this research is to know whether the scout student activity units takes effect to the scout students honest character development of Riau University. The methodology in this research is Descriptive Qualitative. The population of this research is all the active scout members front group Riau University 2016 which amount to 80 people. The result of recapitulation found that the respondents are dominant to choose the statemen” unberdened on doing something “ which are 64 respondents or 80%, while the less dominant is the statement “ being honest and polite to parents “ which are 5 respondents or 6.25%. If the data becomes a benchmark is very often (SS) and often (S) so the total is 80,41%. Therefore, it can be concluded that the level of honesty of scout student activity units is in the very good level.